Understanding interactions between lignin and ionic liquids with experimental and theoretical studies during catalytic depolymerisation - Singh, Sandip Kumar; Banerjee, Subhrashis; Vanka, Kumar; Dhepe, Paresh Laxmikant (Catalysis Today, 2018)
Compared to H2SO4, Bronsted acidic ionic liquid (BAIL, [C3SO3HMIM][HSO4]) catalyzed depolymerization of lignin yielded higher concentration of low molecular weight products under mild conditions (120 degrees C) as proven by GC and GC-MS. To comprehend this disparity in catalytic activity among H2SO4 and BAIL (at similar H+ concentration), experimental techniques [1D(H-1) NMR, 2D(N-15/H-1 HMBC) NMR and RAMAN] have been employed. Based on these studies, it has been proven that the transfer of electron density from substrate to the electron deficient imidazolium ring via formation of hydrogen bond between -OH/OCH3 (substrate) and -N1C2H2N3-(cation) is possible, while the anion plays an important role. Further, density functional theory (DFT) calculations also corroborated this fact by showing a change in the bond angle and decrease in bond length (C-2-H-2 in imidazole), due to the presence of weak and strong hydrogen bonding between the substrate and IL.